"Are we shootin' people or what?": critical reflections of war in popular films / Jamaluddin Aziz, Mohd Nor Shahizan Ali and Fuzirah Hashim - Aziz, Jamaluddin; Shahizan Ali, Mohd Nor; Hashim, Fuzirah (CMIWS and UiTM Press, 2011)
One important and influential popular culture product is fiction film. Arguably, even though fiction film is often seen as a mere entertainment outlet, its undeniable status as a socio-cultural commentator allows fiction films to impart values as well as capture popular imagination and consciousness. Fiction films, needless to say, can move or provoke the audience with their depiction of and focus on real-life events such as personal angst, the World Wars, the cold war, political struggles, economic downturns and natural disaster. One prevailing trend with regards to fiction film is that after the event of September 11, 2001, the interest in the war film genre gains its momentum. Speculations about the post-September 11war that ensued, such as that in Iraq, have allowed variegated representations of war to be made on silver screen, either reaffirming or challenging the audience's perception of war. Employing close textual analysis, the main aim of this paper is to reveal the prevalent themes of some war films. This is done by focussing on the characters. This approach to film as signifying practices will help illuminate the themes of the films, hence, prompting critical reflections of the film's commentary of the war that it alludes to.